Pirbenicillin, a New Semisynthetic Penicillin with Broad-Spectrum Activity - Bodey, Gerald P. (1976)
Pirbenicillin is a new semisynthetic penicillin which inhibited 67% of isolates of Proteus aeruginosa tested in our laboratory, 93% of P. mirabilis, 31% of Enterobacter spp., 41% of Serratia spp., and 58% of Escherichia coli at a concentration of 6.25 μg/ml. Its activity appeared to be inoculum dependent and it was virtually inactive against 10(7) inocula of P. aeruginosa. It was more active than carbenicillin or ticarcillin, but less active than BL-P1654 against P. aeruginosa. Carbenicillin and ticarcillin appeared to be more active than pirbenicillin against Proteus spp., but pirbenicillin was active against some isolates of Klebsiella spp.